CHARACTERISATION OF COWPEA GENOTYPES BASED ON QUANTITATIVE DESCRIPTORS - MAKANUR, BASAVARAJ; V. K. DESHPANDE,; B. S. VYAKARANAHAL, (The Bioscan, 2013)
An experiment was conducted to characterise 35 cowpea genotypes using different quantitative descriptors at plant level. Highly significant differences were obtained among the genotypes for all characters under study. Based on the variation obtained, 35 genotypes were grouped into different categories. All characters were found stable and reliable for classification except for characters number of pods per peduncle and seed yield per hectare. Hence, it’s reliable to consider these stable characters in future breeding programmes of cowpea crop and quality seed production and also in protection in plant variety.